LITERASI WAKAF UANG DI LINGKUNGAN TK AISYIAH 32 KOTA MALANG - Rifa’i, Mochamad Novi; Amalia, Rahmi; Millatina, Afifah Nur (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2023)
Purpose of the study: The purpose of this activity is to increase cash waqf literacy in the TK Aisyiah 32 Malang City Methodology: Implementation methods that refer to the mutually agreed upon analysis of the program situation are discussions, outreach, interactive dialogues, as well as the cash waqf practices of the participants Main Findings: There are still many people in the TK Aisyiah 32 Malang City who do not know about cash waqf, what is known to the waqf participants can only be in the form of land, graves and buildings Applications of this study: This service is useful for the Community in the Aisyiah 32 Kindergarten Environment in Malang City to be able to know and increase literacy regarding cash waqf Novelty/Originality of this study: Communities in the TK Aisyiah 32 environment in Malang City can improve literacy regarding cash waqf